2010
DOI: 10.5539/elt.v3n2p175
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Interaction and Language Output

Abstract: This study investigates the effects of classroom interactions between a) students and students and b) students and teachers on the learning of English passivization by L1 Chinese adult learners of English as a foreign language during the language input and output treatments. In phase 1, both groups were asked to read and underline the input material. After the materials were collected, the participants were required to produce the first reconstruction. After having been exposed to the same input material again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 16 publications
(20 reference statements)
1
27
0
1
Order By: Relevance
“…Thus, the Interaction Hypothesis suggests that interaction between a non-native speaker and a native speaker or among non-native speakers creates acute second/foreign language acquisition environment where learners learn through negotiation of meaning. Furthermore, research has shown that input alone is not as effective as interactional modified input in helping language teaching and learning (Ellis & Fotos, 1999;Gass & Varonis, 1994;Wang & Castro, 2010). Thus, the Interaction Hypothesis plays a central role in learning through conversational interaction on improving language learners' speaking skills.…”
Section: B Long's (1981) Interaction Hypothesismentioning
confidence: 99%
“…Thus, the Interaction Hypothesis suggests that interaction between a non-native speaker and a native speaker or among non-native speakers creates acute second/foreign language acquisition environment where learners learn through negotiation of meaning. Furthermore, research has shown that input alone is not as effective as interactional modified input in helping language teaching and learning (Ellis & Fotos, 1999;Gass & Varonis, 1994;Wang & Castro, 2010). Thus, the Interaction Hypothesis plays a central role in learning through conversational interaction on improving language learners' speaking skills.…”
Section: B Long's (1981) Interaction Hypothesismentioning
confidence: 99%
“…More evidence can be found in many empirical studies for the linking role of interaction (Long, 1983b;Krashen, 1985;Ellis, 1994;Mackey, 1999;Gass, 2003;Mackey, 2006;Wang & Carolyn, 2010).…”
Section: Research On Interaction and Language Output In Foreign Countmentioning
confidence: 99%
“…Ellis (2008), Littlewood & Yu (2011) andMusumeci(1996 support that teacher talk provides planned or semi-structured language input for the students. Therefore, many scholars concur with this apparently logical notion that teachers should provide the students with as much target language input as possible if foreign language acquisition is to occur (see Ahmadi &Panahadeh, 2016;Bahrani, 2013;Ellis, 1994;Duff & Polio, 1994;Krashen, 1982;Littlewood & Yu, 2011;Tang, 2011;Turnbull, 2001;Wang, 2010;Yaqubi&Pouromid, 2013).…”
Section: Introductionmentioning
confidence: 98%